Esej o ironii filozoficznej Teodora Metochity Ὅτι πᾶσι σύνηθες τοῖς σοφοῖς εἰρωνεία καὶ τὸ χαριεντίζεσθαι, καὶ Πλάτωνι μάλιστα καὶ Σωκράτει: Η' - Glinicka , Małgorzta (Hybris, 2014)
This is a translation of Theodore Metochites’s essay concerning philosophical irony from the Hypomnematismoi kai semeioseis gnomikai (Annotations and gnomic notes), an excellent collection of 120 texts on history, literature and thinking, containing the most extensive commentary on Aristotelian philosophy of the late Byzantine period. The essay on philosophical irony – never translated in Poland – is a commentary on the Dialogues of Plato, which had an important influence on the Platonic renaissance of the 15th century. Metochites, growing up in the cultural center of Constantinople, was a prolific writer, leaving behind works of rhetoric, poems, a literary testament, a collection of philosophical texts and two works on astronomy.